2016
DOI: 10.1371/journal.pone.0161279
|View full text |Cite
|
Sign up to set email alerts
|

Do Changes in Current Flow as a Result of Arrays of Tidal Turbines Have an Effect on Benthic Communities?

Abstract: Arrays of tidal energy converters have the potential to provide clean renewable energy for future generations. Benthic communities may, however, be affected by changes in current speeds resulting from arrays of tidal converters located in areas characterised by strong currents. Current speed, together with bottom type and depth, strongly influence benthic community distributions; however the interaction of these factors in controlling benthic dynamics in high energy environments is poorly understood. The Stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Moreover, impacts on benthic communities is also an ongoing topic of research. However, the effect of tidal energy extraction on benthos might be negligible, since their composition is stable over an approximate 1 m/s range of velocities in high‐velocity flow environments (Kregting et al, ), which is above the range of changes we found; an overall habitat loss might instead be predicted to occur in response to climate change.…”
Section: Discussionmentioning
confidence: 63%
“…Moreover, impacts on benthic communities is also an ongoing topic of research. However, the effect of tidal energy extraction on benthos might be negligible, since their composition is stable over an approximate 1 m/s range of velocities in high‐velocity flow environments (Kregting et al, ), which is above the range of changes we found; an overall habitat loss might instead be predicted to occur in response to climate change.…”
Section: Discussionmentioning
confidence: 63%
“…The entrance to the south basin is a long narrow channel known as the Narrows, where current tidal velocity reaches ~3.5 m/s (Kregting & Elsäβer, ). It is typified by an exposed bedrock substratum (Kregting et al, ) that spills out into the south basin where a range of substrates can be found, depending on water flow velocity.…”
Section: Methodsmentioning
confidence: 99%
“…Noise levels produced by two sub-sea tidal turbines were assessed in the Narrows tidal [29]. The seafloor of the Narrows consists of cobbles and small to large boulders on a bedrock base layer, with flow rates at the turbine sites reaching approximately 2 ms -1 [30]. The two tidal turbines considered in this study were the ¼ scale Deep Green sub-sea turbine developed by Minesto (see [13] for full details on this device, referred to herein as the 'kite'), and the full-scale SCHOTTEL IST device ( [8] referred to herein as 'schottel').…”
Section: Study Site Turbine Devices Investigated and Ambient Sound mentioning
confidence: 99%
“…Current velocities were measured with a seabedmounted broadband 600 kHz RDI Teledyne Workhorse Monitor Acoustic Doppler current profiler (ADCP) installed approximately 30m from the kite's position. Bathymetry data was obtained from the Strangford Lough hydrodynamic model [33] and sediment properties were obtained from [30].…”
Section: Calculating Listening Space Reductionsmentioning
confidence: 99%